Applied Behaviour Analyze Method Increase Social Interaction Children With Autisme, 2-5 Years Old - Khoridatul Bahiyah; Ah. Yusuf; Sri Kusmawati (Jurnal Ners, 2008)
Introduction: Autism is social interaction disorder in children. They were seemingly living in their own world. ABA method was a technique to decrease behaviour disorder or social interaction in autism children. The aimed of this research was to evaluate correlation between ABA method implementation and parents role with social interaction development in children with autism.Methods: This research was used a cross sectional with purposive sampling. There  were 22 respondents who met to the inclusion criteria. The independent variable was ABA methode and the dependent variable was social interaction development. Data were collected by using questionnaire and observation, then analyzed by using Spearman Rho Correlation with significance level α≤0.05.Results: The result showed that there was a correlation between ABA method and social interaction development in autism children with p<0.30.Conclution: It can be concluded that ABA method has a correlation with social interaction in autism children. It is recommended that ABA method can be used as a technique to decrease social interaction disorder on autism children.